Challenges of using ICT in assessing and developing students' affective domain in education - Abdulfatai, Ismail; Ismail, Nik Ahmad Hisham; Abdullahi, Hussein Osman (International Foundation for Research and Development (IFDR), 2014)
ICT is becoming an inevitable tool in education nowadays. For any academic activities to be effective the use of ICT is imperative. There are also a lot of benefits and improvement that ICT has brought to the field of education. These benefits and development cut across all spheres of education, such as the aspect of content, instruction and evaluation. In area of evaluation, the cognitive and psychomotor aspects of evaluation are mostly developed, based on the fact that both can be easily accessed through ICT. However, in the aspect of affective domain, the level of assessment is low and not absolutely reliable becausee it delas with the feelings, interest and values that leaner attached to the subject matter. Hence, this study aimed at finding an effective way that ICT can be used to access students' affective domain in the process of evaluation. In order to get in-depth understanding of the subject matter, the study employs qualitative design by using semi-structured interview to elicit information from specialists in the field of communication technology. Finding from the study indicates that the use of ICT to evaluate student affective domain requires an illustrious, diligent, and enthusiastic ICT literate teacher. Equally, there is a need to develop software that will focus more on the evaluation of students' affective domain. Meanwhile, this area that will develop students' soft skill is greatlyy needed to produce good citizens, employees, and government of their individual community.